Pathophysiological Role of Nucleic Acid-Sensing Pattern Recognition Receptors in Inflammatory Diseases - Kano, Norisuke; Ong, Guang Han; Ori, Daisuke; Kawai, Taro (Frontiers in Cellular and Infection Microbiology, 2022)
Pattern recognition receptors (PRRs) play critical roles in recognizing pathogen-derived nucleic acids and inducing innate immune responses, such as inflammation and type I interferon production. PRRs that recognize nucleic acids include members of endosomal Toll-like receptors, cytosolic retinoic acid inducible gene I-like receptors, cyclic GMP–AMP synthase, absent in melanoma 2-like receptors, and nucleotide binding oligomerization domain-like receptors. Aberrant recognition of self-derived nucleic acids by these PRRs or unexpected activation of downstream signaling pathways results in the constitutive production of type I interferons and inflammatory cytokines, which lead to the development of autoimmune or autoinflammatory diseases. In this review, we focus on the nucleic acid-sensing machinery and its pathophysiological roles in various inflammatory diseases.